Multiple drug abuse with zopiclone, diazepam, gabapentin: case report - Özcan, Halil; Özcan, Elif; Üstündağ, Mehmet Fatih; Yücel, Atakan (Journal of Dependence, 2025)
Multiple drug abuse is a common phenomenon within drug addiction. In many cases, individuals use two, three, or more psychoactive substances, usually from different drug groups, simultaneously. A 34-year-old non-Turkish woman was diagnosed with anxiety disorder and began paroxetine 20-40 mg/day eight years ago in her home country. At a later date, gabapentin and zopiclone were added to her treatment. The patient, who had abused zopic-lone and gabapentin for four years and was no longer able to obtain them, came to our outpatient clinic. Treatment with diazepam was begun and it was observed that she was also misusing it. Unable to adjust to her new treatment, she failed to return for follow up. Due to a number of different factors, we believe that this case, in which the patient abused two different benzodiazepines and one antiepileptic, can contribute to the literature.